Explant liver evaluation decodes the mystery of cryptogenic cirrhosis!. Issue 1 (30th May 2019) - Jain, Mayank; Venkataraman, Jayanthi; Varghese, Joy; Vij, Mukul; Reddy, Mettu S; Rela, Mohamed
Abstract : Background and Aim: To determine the concordance of liver explants with the pretransplant diagnosis. Methods: This was a retrospective analysis of 251 liver explants. Patient information included demography, comorbidity, and etiological diagnosis. Final diagnosis was based on morphological and histological findings. For non‐alcoholic steatohepatitis (NASH) and cryptogenic cirrhosis, we investigated comorbid states such as obesity, hypertension, and diabetes. Chi square test and Cohen's Kappa value were used. A P value of <0.05 was considered significant. Results: A total of 192 patients (76.5%) were males. A significant concordance of explant diagnosis with pretransplant diagnosis was present in 225 (89.6%) patients. It was 100% for alcohol‐related disease, hepatitis B, hepatitis C, autoimmune (AI) liver disease, biliary cirrhosis, and Budd–Chiari syndrome. Of 37 patients with a pretransplant diagnosis of cryptogenic cirrhosis, major discordance was observed in 23 (62.1%). On explant, seven patients each had hemochromatosis 5 (13.5%), AI hepatitis, and NASH (18.9%); two had noncirrhotic fibrosis (5.4%); and one each had Wilson's disease and congenital hepatic fibrosis (2.7%). Of the 20 explants, 3 with pretransplant diagnosis of NASH had a diagnosis of cryptogenic cirrhosis on explant specimens. Cohen's Kappa for the concordance of pretransplant diagnosis and explant diagnosis in NASH and cryptogenic cirrhosis patients was 0.75 and 0.47, respectively. An incidental hepatocellular carcinoma was picked up in 16 explants, and 18 had granulomas. Conclusion: Concordance between pretransplant and explant diagnosis is lower for NASH and cryptogenic cirrhosis. The true prevalence of cryptogenic cirrhosis in our study was 5.6%. Abstract : A significant concordance of explant diagnosis with pretransplant diagnosis was present in alcohol, hepatitis B, hepatitis C, autoimmune liver disease, biliary cirrhosis, and Budd–Chiari syndrome. For 37 patients with a pretransplant diagnosis of cryptogenic cirrhosis, major discordance was observed in 23 (62.1%). Cohen's Kappa for concordance of pretransplant diagnosis and explant diagnosis in non‐alcoholic steatohepatitis and cryptogenic cirrhosis patients was 0.75 and 0.47, respectively. An incidental hepatocellular carcinoma was observed in 16 explants, and 18 had granulomas.